Impact and Acceptance of Digitalization in the Indonesian Workplace - HR, Lis Andriani; Kesumah, Fajrin Satria Dwi; Huzaimah, RA Fiska (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Digitalization has changed organizational dynamics and greatly improved operational efficiency in the workplace. Digitalization brings difficulties even with its benefits, especially with employee technological acceptability. This paper aims to investigate how digitalization affects employee productivity and workplace efficiency and to find elements influencing workers' technology adoption. A survey was conducted among 169 employees across various organizations in Indonesia, analyzing their perceptions of the usefulness, ease of use, and management support for digital technologies. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The study indicated that perceived usefulness is much influenced by perceived ease of use, which highly predicts technological uptake. While simplicity of use alone does not greatly affect acceptance without the acknowledged utility, management support is vital in helping the acceptance of technology. For digitalization to be effective, companies have to make sure staff members view these technologies as helpful in addition to using simple, user-friendly solutions. Technology adoption depends on a favorable environment, greatly fostered by management support.